PELAKSANAAN PEMBELAJARAN DARING DI MASA PANDEMI COVID 19 - Ela Febriani; Nina Kurniah (DIADIK, 2023)
This study aims to describe the implementation of online learning during COVID-19 pandemic at TK Pertiwi II Bengkulu City. The type of study used in this research is descriptive qualitative research. Data collection methods used are interviews, observation and documentation. The data sources are teachers, school principals and parents at TK Pertiwi II and documentation in the form of learning devices used during COVID-19 pandemic. The data analysis technique used is data reduction, recording the results of interviews with teachers, school principals, and parent of students, recording coding of data according to the information provided by informants, displaying data outlining the results of interviews with school principals, teachers and parents and verifying data thinking about reviewing the results of interviews, reviewing field notes, rethinking observational data and findings in the field, in order to draw conclusions from the results of research that has been done. The results of this study describe the implementation of online learning during covid-19 pandemic which is carried out at TK Pertiwi II carried out online